Symbols in the plays of Noordin Hassan - Rohani binti Md. Yousoff (International Institute of Islamic Thought and Civilization (ISTAC), International Islamic University Malaysia, 2010)
The works of National Laureate Noordin Hassan must be looked at in the light of his life as a historic route of occasions, coloured by his past, his richness of experiential content. His emotions draws on the past to form the present, most often presented through symbols. The responses and reference to the meaning of the symbols should give the additional effect and room for analysis. The constructs of knowledge, awareness and meaning is realized by integrating the multiple perspectives derived from the use of 'self' as part of the context of analysis. Noordin's process of knowing and its end product, his plays, are based on, and subject to a time and space dimension that affects the way he knows and the way he produces his works. Time and space influence the nature of his thinking methods and the nature of the knowledge. This study hopes to explore the use of symbols in five of his plays supported by intertextual references to his other works. The dissertation shall begin with his background: his origin, education and the influences on his life that have contributed to ideas for the plays. Analysis of the texts and interviews with the playwright shall reveal the sources of his ideas and inspiration to reveal the soul of a most prolific Islamic playwright. This dissertation also hopes to give insights into the philosophy behind the symbols found in the works of the first playwright to receive the Sasterawan Negara (National Literary) award in 1995. The frame of reference is within a specific environment of religion and tradition. As Noordin's plays should not be limited to Malay theatre practitioners but to be read and understood as works of an Islamic and traditional thinker, all five of his plays under study have been translated.